2021
DOI: 10.1002/onco.13767
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Out-of-Pocket Costs and Financial Toxicity During Early-Phase Oncology Clinical Trials

Abstract: Background. Clinical trials are an important therapeutic option for cancer patients. Although financial burden in cancer treatment is well-documented, the financial burden associated with clinical trials is not well understood. Patients and Methods. We conducted a survey regarding economic burden and financial toxicity in cancer patients enrolled in Phase I clinical trials for >1 month. Financial Toxicity Score (FTS) was assessed using the Comprehensive Score for Financial Toxicity (COST) survey. Patients also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 32 publications
1
42
1
Order By: Relevance
“…Regarding disease characteristics, advanced cancer and receiving targeted therapy are both risk factors for FT. Advanced nasopharyngeal cancer requires more systemic treatments, such as innovative drugs and diagnostic methods, thereby directly increasing the medical costs ( 33 ). Nevertheless, several studies ( 11 , 34 , 35 ) have suggested that indirect medical costs for cancer treatment, such as transportation, accommodation, and time expenditure can also contribute to the FT of cancer survivors, but we did not observe significant association between travelling distance to the hospital and FT levels. The impact of indirect costs is limited probably due to the current convenience in transportation, as well as coverage of high-speed railway and subway in the areas where we conducted our survey.…”
Section: Discussioncontrasting
confidence: 97%
“…Regarding disease characteristics, advanced cancer and receiving targeted therapy are both risk factors for FT. Advanced nasopharyngeal cancer requires more systemic treatments, such as innovative drugs and diagnostic methods, thereby directly increasing the medical costs ( 33 ). Nevertheless, several studies ( 11 , 34 , 35 ) have suggested that indirect medical costs for cancer treatment, such as transportation, accommodation, and time expenditure can also contribute to the FT of cancer survivors, but we did not observe significant association between travelling distance to the hospital and FT levels. The impact of indirect costs is limited probably due to the current convenience in transportation, as well as coverage of high-speed railway and subway in the areas where we conducted our survey.…”
Section: Discussioncontrasting
confidence: 97%
“…The studies of psychological distress have focused on emotional problems (eg, anxiety, depression) and physical problems (eg, fatigue), and studies on financial toxicity are mostly based on demographic factors such as age, with little attention to treatment-related factors. 18 , 19 , 20 , 21 , 22 The above topics are less frequently researched in China. Approximately 85% of patients choose public hospitals for treatment, and cancer patients prefer high-level public hospitals in China.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, existing evidence suggests that increased socioeconomic diversity of the physician workforce improves the quality of patient care; our findings may reflect that diversity among clinical trainees and faculty is associated with greater cost conscicousness and advocacy for patients [ 35 ]. As financial burden disproportionately impacts minority patient populations, ensuring diversity in trainee socioeconomic backgrounds may ultimately help to mitigate outcomes disparities [ 6 , 36 ]. Unfortunately, a significant socioeconomic diversity gap persists in medical education, perpetuated both by substantial increases in the costs of medical school attendance and inherent difficulties in assessing socioeconomic background as a less visible form of diversity in the applications process [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%